Greek Perspectives on Cyrus and his Conquests - Clothier, Stephen (My University, 1997)
The aim of this paper is to examine the figure of Cyrus II of Persia, as it appears in The Histories of Herodotus and Xenophon's Cyropaedia. The author's primary concern is the historical background of the narratives, rather than their literary aspects. An attempt will be made to relate the various episodes in the Greek works to the cuneiform evidence, which is quite substantial with respect to the capture of Babylon. An examination of the cuneiform evidence (in translation) will form the main topic of the first chapter. Chapter Two will focus on the Herodotean account of Cyrus, which is the most important one to survive from the Classical world. Although the presence of various heroic motifs render substantial portions of the narrative questionable, these will nevertheless be examined in the light of the many parallels that have been found for them in the Near East and Greece itself. Also, an attempt will be made to uncover the historical truths that are quite possibly hidden beneath the mythic façade. Moreover, in the pursuit of reliable traditions, the differences and similarities between the Greek accounts and the cuneiform records will be noted. The same method will be used in the third chapter, which focuses on The Cyropaedia. Because of the largely fictitious character of this work, however, only those sections which can be related to historical events will be examined in any detail. A reconstructed biography of Cyrus, based on all viable evidence, will form the bulk of the concluding chapter. At this point the testimony of other Greek historians, most notably Ctesias, will be examined. My own views on the proper reconstruction of events will be fully expounded, but dissenting opinions will also be noted. It is inevitable that opinion be sharply divided when the relevant texts are either ambiguous or fragmentary.
Keywords: Classics; Classics